Optimization of Nano-Silica Content for Enhanced Mechanical Properties of Concrete - Harish, V.; Reddy, B. Sudharshan (Journal of Neonatal Surgery, 2025)
The impact of adding nano-silica (NS) to concrete of M40 grade on its mechanical characteristics is examined in this study. At 7, 28, 56, and 90 days, the compressive, flexural, and split tensile strengths of concrete mixes containing nano-silica contents ranging from 0% (control) to 1.5% by weight of cement were assessed. Results demonstrate a consistent and significant enhancement in mechanical performance with increasing nano-silica dosage. At 1.5% NS, compressive strength increased by approximately 22–24%, flexural strength by 11.8–13.3%, and split tensile strength by 12.5–13.9% compared to the control mix across all curing ages. The improvement is attributed to the pozzolanic activity of nano-silica, which promotes the production of calcium silicate hydrate (C-S-H) gel, accelerates hydration, and refines the microstructure and interfacial transition zone (ITZ). According to these results, nano-silica is a useful ingredient for creating high-performance concrete with exceptional strength and durability properties.